PENINGKATAN KREATIVITAS BELAJAR MATEMATIKA MELALUI PEMBELAJARAN PROBLEM SOLVING - Wanda Nugroho Yanuarto (De Fermat : Jurnal Pendidikan Matematika, 2019)
The aim of this research’s are : 1) giving opportunity for asking the material what given by the lecturer, 2) giving the alternative how to solve the problem, 3) giving the stimulus of the student for show and understanding the idea, 4) giving the opportunity for see and find the giving solution of problem and 5) giving the stimulus to take the resk. This research is use the Problem Solving Education for increasing the creativity of study math in Mathematic subject in Muhammadiyah University of Purwokerto. And the result of this research’s are : 1) Reaching the knowledge of understanding the material of mathematic, 2) have the skill of show their suggestion and respecting some suggestion of their friends, 3) have the knowledge to see and problem solving to do the exercise of mathematic, 4) have the ability of showing their suggestion, and 5) have the ability to take a resk and improving their ability for solving some problems in mathematic it self.